Changes in microbial diversity and volatile metabolites during the fermentation of Bulang pickled tea - Zhou, Jinping; Chen, Laifeng; Foo, Hooi Ling; Cao, Zhenhui; Lin, Qiuye (Elsevier Ltd, 2024)
The present study aimed to determine microbial community, short-chain fatty acids (SCFAs), and volatilome of Bulang pickled tea during fermentation. Sequencing of 16S rRNA and ITS revealed that Bualng pickled tea was dominated by Lactobacillus plantarum, unclassified Enterobacteriaceae, unclassified Debaryomyces, Candida metapsilosis, Cladosporium sphaerospermum, and unclassified Aspergillus. The overall contents of SCFAs increased, with acetic acid showing the highest content. A total of 398 differential volatile metabolites were detected using differential metabolomics analysis. Out of these different volatile compounds, ten key volatile compounds including (Z)-4-heptenal, 1-(2-thienyl)-ethanone, 5-methyl-(E)-2-hepten-4-one, 2-ethoxy-3-methylpyrazine, p-cresol, 2-methoxy-phenol, ethy-4-methylvalerate, 3-ethyl-phenol, p-menthene-8-thiol, and 2-s-butyl-3-methoxypyrazinewere were screened based on odor activity value (OAV). The Spearman correlation analysis showed a high correlation of SCFAs and volatile compounds with microorganisms, especially L. plantarum and C. sphaerospermum. This study provided a theoretical basis for elucidating the flavor quality formation mechanism of Bulang pickled tea.